2010
DOI: 10.1080/00224490903402538
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Anal Sexuality and Anal Sex Behaviors: A Review

Abstract: Little research addresses the role of anal sexuality and anal sexual behaviors as a widely practiced but relatively less frequent element of a heterosexual sexual repertoire. However, the importance of anal sex in sexual health is increasingly well-defined by epidemiological and clinical studies. This article reviews existing data on a range of heterosexual anal sex practices and provides conceptual and methodological recommendations for new research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
127
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 73 publications
4
127
1
Order By: Relevance
“…Although research is scarce in this area, there is a growing body of literature which outlines the increasing prevalence of anal sexual practices among younger adults, with the peak in 30‐34 year olds 21, 22, 43. Studies indicate engagement in anal sexual behaviors has increased over time, with some lifetime prevalence estimates for heterosexual anal intercourse as high as 40% 21, 22, 43.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although research is scarce in this area, there is a growing body of literature which outlines the increasing prevalence of anal sexual practices among younger adults, with the peak in 30‐34 year olds 21, 22, 43. Studies indicate engagement in anal sexual behaviors has increased over time, with some lifetime prevalence estimates for heterosexual anal intercourse as high as 40% 21, 22, 43.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate engagement in anal sexual behaviors has increased over time, with some lifetime prevalence estimates for heterosexual anal intercourse as high as 40% 21, 22, 43. There is also suggestion that condom use with anal sex compared to vaginal sex is lower in heterosexuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us take one example to illustrate the point: anal sex is undeniably part of the contemporary heterosexual repertoire, with c40% reporting at least one experience, and 10% (in both UK and US studies) reporting anal sex within the last three months (Javanbakht et al, 2010) to a year (McBride & Fortenberry, 2010). There are indications that prevalence is increasing (Gindi et al, 2008;McBride & Fortenberry, 2010).…”
Section: Unpacking Heterosexualitymentioning
confidence: 99%
“…Meanwhile, condom usage among heterosexuals reporting anal sex tends to be low (c.60% never use), while the same individuals are also more likely to report a history of STIs (Hensel et al, 2010;Javanbakht et al, 2010;McBride & Fortenberry, 2010). Studies in New York found only 38.3% of heterosexual men reported condom use at last sex compared to 62.9% of MSM (Pathela et al 2011) while only 23% of heterosexuals used condoms during anal sex, compared to 61% of MSM (The Body, 2010).…”
Section: Unpacking Heterosexualitymentioning
confidence: 99%